KEANEKARAGAMAN PERIFITON DI SUNGAI BELAWAN KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA Diversity of Periphyton in the Belawan River Subdistrict Pancur Batu Regency Deli Serdang North Sumatera - Camelina Simbolon; Miswar Budi Mulya; Desrita Desrita (AQUACOASTMARINE, 2016)
Activities that occur around Belawan River will generate waste and impact on the physical and chemical factors that affect the aquatic organisms that periphyton. This study aims to specify the diversity of Periphyton in the Belawan River and to specify condition Belawan River judging from the chemical physics factors. Furthermore, Physical, chemical and Biologycal parameters was observed factors of the temperature, flow velocity, transparency of waters, pH, TSS, DO, BOD5, nitrates, orthophosphates and Diversity of Periphyton. The observations were made three times in three the research station. Sampling taking carried is three time repetitionon each station. Based on the result acquired that index diversity of periphyton ranged between 2,72 to 2,84 ind/cm2 and the Abundace of periphyton ranged between 763 to 1684 ind/cm2. Temperatures value ranged between 26 to 29 oC, flow velocity ranged between 0,4 to 0,7 m/s, transparency of waters ranged between 25 to 50 cm, pH ranged between 7,3 to 7,6, DO ranged between 3,5 to 4,0 mg/l, BOD5 ranged between 1,4 to 2,8 mg/l, TSS ranged between 11,33 to 38,5 mg/l, nitrates ranged between 1,0 to 1,9 mg/l dan orthophosphates ranged between 0,03 to 0,078 mg/l. based on the Shanon’s index of diversity (H’) and physival-chemical factors in the Belawan River were classified as into mild pollution criterion.Keywords: Periphyton, Abundance, Diversity, River Belawan